Antimicrobial Orthodontic Wires Coated with Silver Nanoparticles - Gonçalves,Isabella Salgado (2020)
Abstract Conventional orthodontic treatment with the use of stainless steel may be detrimental to oral health by promoting demineralizing lesions appearance and increasing adhesion and formation of bacterial biofilm, inducing the development of cavities. An alternative that has been researched to reduce the side effects of orthodontic treatment is the coating of materials with antimicrobial nanoparticles. Nanometric- sized particles increase their surface area and contact with the microbial membrane, consequently intensifying their bacteriostatic and bactericidal effect. In this work, hydrothermal synthesis, a “green” process was used to attach silver nanoparticles (AgNPs) to the surface of two different brands of orthodontic wires. The coated materials were analyzed for their physicochemical properties by scanning electron microscopy (SEM), X-ray diffraction (XRD) and differential scanning calorimetry (DSC), which showed the distribution of AgNPs along the wires without modifying their properties. In the microbiological test, one of the brands showed a statistically significant difference in microbial adhesion and biofilm formation by Staphylococcus aureus and Streptococcus mutans. Results lead to the conclusion that antimicrobial orthodontic wires coated with silver nanoparticles through hydrothermal synthesis is a promising material for the improvement of orthodontic treatment.